Advances in Biocultural Approaches to Understanding Stress in Humans - Elizabeth Bingham Thomas; Nicolette M. Edwards; Jaxson D. Haug; K. Ann Horsburgh (Humans)
This paper outlines advances in biocultural approaches to anthropology by discussing anthropological approaches to understanding stress, how anthropologists have typically measured stress, and why it matters for anthropology and beyond. We discuss the application of common quantification techniques such as the Perceived Stress Scale (PSS) and biomarkers of psychosocial stress from abnormal hypothalamic–pituitary–adrenal (HPA) axis activity. We highlight case studies that demonstrate the utility of a biocultural approach to stress across a range of topics—(i) childhood effects, (ii) non-human animals, (iii) depression and anxiety, (iv) migration, and (v) religion—as well as the complexities in the relationship between perceived and biological stress. We conclude by highlighting several areas where we have seen significant advances and point to approaches in other disciplines that anthropology might incorporate to its benefit.